CCR2+ monocytic myeloid‐derived suppressor cells (M‐MDSCs) inhibit collagen degradation and promote lung fibrosis by producing transforming growth factor‐β1. Issue 3 (21st September 2017) - Lebrun, Astrid; Lo Re, Sandra; Chantry, Mathilde; Izquierdo Carerra, Xavier; Uwambayinema, Francine; Ricci, Doriana; Devosse, Raynal; Ibouraadaten, Saloua; Brombin, Lisa; Palmai‐Pallag, Mihaly; Yakoub, Yousof; Pasparakis, Manolis; et al.
Abstract: Monocytes infiltrating scar tissue are predominantly viewed as progenitor cells. Here, we show that tissue CCR2 + monocytes have specific immunosuppressive and profibrotic functions. CCR2 + monocytic cells are acutely recruited to the lung before the onset of silica‐induced fibrosis in mice. These tissue monocytes are defined as monocytic myeloid‐derived suppressor cells (M‐MDSCs) because they significantly suppress T‐lymphocyte proliferation in vitro . M‐MDSCs collected from silica‐treated mice also express transforming growth factor (TGF)‐β1, which stimulates lung fibroblasts to release tissue inhibitor of metalloproteinase (TIMP)‐1, an inhibitor of metalloproteinase collagenolytic activity. By using LysMCreCCR2 loxP / loxP mice, we show that limiting CCR2 + M‐MDSC accumulation reduces the pulmonary contents of TGF‐β1, TIMP‐1 and collagen after silica treatment. M‐MDSCs do not differentiate into lung macrophages, granulocytes or fibrocytes during pulmonary fibrogenesis. Collectively, our data indicate that M‐MDSCs contribute to lung fibrosis by specifically promoting a non‐degrading collagen microenvironment. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.